Laser‐Induced in situ Synthesis and Assembly of Nano‐Cotton TiO2 Humidity Sensors with High Sensitivity and Fast Response for Real‐Time Respiratory Monitoring - Zhichao Yu; Juqing Li; Qiurui Zhang; Pei Xiang; Jincheng Lei (Small Structures)
Humidity sensors functioned by 1D nanostructural metal oxides (1D NMOs) are promising for real‐time respiratory monitoring. However, the preparation and assembly of 1D NMOs on sensor structures are quite challenging due to the complicated synthesis procedures and vulnerability of nanomaterials. Herein, a multi‐laser processing technology is developed to fabricate nano‐cotton TiO2 humidity sensors for respiratory monitoring. The nano‐cotton TiO2 is in situ synthesized and assembled to the interdigitate electrodes of the sensor structure using the transmitted picosecond laser deposition. The as‐deposited TiO2 layers are in situ post‐annealed by a CO2 laser to optimize the crystallinity and phase compositions for humidity sensing. By investigating the evolution mechanism of the nanostructures of the laser‐induced plasma plumes during sputtering, it is demonstrated that the nanostructures of the laser‐deposited TiO2 layers can be flexibly controlled by varying the target‐to‐substrate distance. The crystallinity, phase composition, surface roughness, and layer thickness of the nano‐cotton TiO2 are estimated to evaluate the developed technology. The fabricated sensors exhibit high sensitivity and rapid response to the variation of relative humidity under both steady and transient states. To demonstrate for real‐time respiratory monitoring, the fabricated sensor is integrated into a commercial mask to monitor human's breathing under different respiratory modes.